TINJAUAN TERHADAP PELAKU BODY SHAMING BERDASARKAN UNDANG-UNDANG NOMOR 19 TAHUN 2016 PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Rizky Fadhila (Journal of Law ( Jurnal Ilmu Hukum ), 2019)
AbstractNowadays body shaming is rife (insulting body image) among the public, especially on social media, as an effort to guarantee the rights of victims due to body shaming crimes the need for clear legal rules. Considering the legal rules regarding body shaming in Law Number 19 Year 2016 Amendment to Law Number 11 Year 2008 Regarding Information and Electronic Transactions (ITE Law) there is a lack of clarity in its regulation which does not mention directly about body shaming, it is necessary to have review of the rules governing body shaming so that it does not cause multiple interpretations in using it. The legal issues in this research are the legal provisions and the application of body shaming criminal acts in terms of the ITE Law. The method used in this study uses normative juridical research methods. Based on the results of the study, the regulation of criminal acts against body image can be referred to using Article 45 paragraph (3) of the ITE Law if the crime is committed through social media, if viewed from the characteristics of body shaming that has fulfilled the objective and subjective elements of the article. , so that body shaming can be said to be a criminal offense of mild humiliation of body image.